Hilbert‐Huang transform based fault identification and classification technique for AC power transmission line protection. (4th August 2020) - Anand, Abhisekh; Affijulla, Shaik
Summary: In the modern power system, the fault identification and classification is one of the challenging tasks during high fault impedance due to low change in the magnitude of fault current from steady‐state to fault inception. In this paper, a high impedance fault detection technique is proposed based on Hilbert‐Huang transform (HHT). The energy for each phase is computed from the intrinsic mode function (IMF) of three‐phase voltage/current signals. An average relay energy index ( AREI ) is proposed to detect the transmission line fault in the large interconnected power system. Furthermore, a fault classification technique is also proposed based on relay energy index ( REI ) of each phase of the three‐phase voltage/current signals. The proposed HHT based fault detection technique is validated on standard WSCC 9 bus and IEEE 14 bus test power systems using PSCAD and MATLAB software. The simulation results reveal that the proposed Hilbert‐Huang transform based fault identification and classification technique can be best suitable for protection of transmission lines during high impedance faults in complex and large AC power transmission system. Abstract : In the modern power system, the fault identification and classification is one of the challenging tasks during high fault impedance due to low change in the magnitude of fault current from steady‐state to fault inception. In this paper, a high impedance fault detection technique is proposed based on Hilbert‐Huang transform (HHT). The energy for each phase is computed from the intrinsic mode function (IMF) of three phase voltage/current signals. An average relay energy index (AREI) is proposed to detect the transmission line fault in the large interconnected power system. Furthermore, a fault classification technique is also proposed based on relay energy index (REI) of each phase of the threephase voltage/current signals. The proposed HHT based fault detection technique is validated on standard WSCC 9 bus and IEEE 14 bus test power systems using PSCAD and MATLAB software. The simulation results reveal that the proposed Hilbert‐Huang transform based fault identification and classification technique can be best suitable for protection of transmission lines during high impedance faults in complex and large AC power transmission system.